2021
DOI: 10.1016/j.adhoc.2021.102539
|View full text |Cite
|
Sign up to set email alerts
|

Interference management for coexisting Internet of Things networks over unlicensed spectrum

Abstract: The main building block of Internet of Things (IoT) ecosystem is providing low-cost scalable connectivity for the radio/compute-constrained devices. This connectivity could be realized over the licensed spectrum like Narrowband-IoT (NBIoT) networks, or over the unlicensed spectrum like NBIoT-Unlicensed, SigFox and LoRa networks. In this paper, performance of IoT communications utilizing the unlicensed band, e.g. the 863-870 MHz in the Europe, in indoor use-cases like smart home, is investigated. More specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another recent study by Azari et al [21] investigated the impact of interference on the performance of 5G networks for IoT applications. The study found that interference can cause significant degradation of network performance, especially for applications that require low latency and high bandwidth.…”
Section: Related Workmentioning
confidence: 99%
“…Another recent study by Azari et al [21] investigated the impact of interference on the performance of 5G networks for IoT applications. The study found that interference can cause significant degradation of network performance, especially for applications that require low latency and high bandwidth.…”
Section: Related Workmentioning
confidence: 99%
“…The combined frequency range depends on a direct transmission in order to mitigate the path loss for the cellular users (CUs) in both Line-of-Sight (LOS) and Non-Line-of-Sight (NLOS) transmission [23]. However, because of the short wavelength as well as several intra-cell interferences by neighboring devices, the frequency bands of B5G suffer from attenuation, fading, reflection, refraction, scattering, shadowing, and absorption by brick walls and concrete buildings, preventing them from penetrating long distances [24,25]. Meanwhile, in ultra-dense network urban areas, users face penetration, scattering, and interference problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main concern in their implementation can be linked to the limited network coverage. In order to solve this concern, Low-Power Wide Area Networks (LPWANs) technologies, such as SigFox and LoRa, have appeared [7,8]. Among the LPWANs technologies, LoRa has gained much more popularity as it provides large network coverage with low deployment cost and power consumption [9].…”
Section: Introductionmentioning
confidence: 99%